Cooperation across Cultures: an Analysis of Intercultural Competence in Development Organizations - Lisa Armbruster (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2014)
Behavior, attitudes, and values differ extremely throughout the world. Whenever two members of different groups such as cultures, nations, or societies interact, such differences become a determining factor for the process of interaction. When thinking of such areas where interactions among members of different cultures constitute a crucial precondition, development cooperation comes to one's mind right away. Development policy and cooperation take place in intercultural settings as members of so-called more developed countries interfere in the development of so-called less developed countries, which always includes a cultural component. Hence, such international and intercultural interactions require a competent way of dealing with cultural differences. Consequently, this paper examines the extent to what intercultural competence is a determining factor for the success of organizations of development cooperation. It does so by analyzing the case of the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) in Bolivia. Bolivia represents a highly interesting context for studies dealing with interculturality as the country has passed a constitution in 2006 which explicitly includes concepts of interculturality (interculturalidad). Accordingly, the concept of intercultural competence is analyzed on (1) the individual level of the employees of GIZ Bolivia, (2) the organizational- structural level, and (3) the level of the organization's context. In a following step the same is done with the concept of success. This then allows linking both concepts which emphasizes that they are closely linked to each other. Thus, subsequently, the paper highlights some recommendations and presents the case study's results in the light of theory by linking the empirical findings and the theoretical framework.
Keywords: 330; Interculturality; Intercultural competence; Development cooperation; Bolivia; GIZ; Entwicklungsorganisation; Deutsch; Interkulturelle Kompetenz; Bolivien; Deutschland